1992
DOI: 10.1111/j.1365-2761.1992.tb01237.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of eggs and yolk sac larvae of halibut, Hippoglossus hippoglossus L.

Abstract: Scanning electron micrographs of halibut eggs with an epiflora dominated by Flexibacter sp., showed ulcerations colonized by large numbers of bacteria. The chorion was dissolved in most ulcerations and the zona radiata was severely damaged. Infection experiments showed that exposure to these bacteria caused high mortalities at the late egg stage, hatching and the early yolk sac stage. Eggs exposed to three different Vibrio spp. showed different mortality patterns, with low mortality at hatching, followed by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
66
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 18 publications
5
66
1
Order By: Relevance
“…It resembles the fish pathogen Flexibacter maritimus, but differs from the latter in a number of biochemical and physiological characteristics. Challenge experiments confirmed that this bacterium is capable of causing mortality in halibut eggs and yolk-sac larvae by penetrating the eggshell (Bergh et al 1992b). It has not been found on hosts other than halibut, despite its ability to cause mortality in the eggs and larvae of cod Gadus morhua (Bergh 2000).…”
Section: Bacterial Diseasesmentioning
confidence: 91%
See 3 more Smart Citations
“…It resembles the fish pathogen Flexibacter maritimus, but differs from the latter in a number of biochemical and physiological characteristics. Challenge experiments confirmed that this bacterium is capable of causing mortality in halibut eggs and yolk-sac larvae by penetrating the eggshell (Bergh et al 1992b). It has not been found on hosts other than halibut, despite its ability to cause mortality in the eggs and larvae of cod Gadus morhua (Bergh 2000).…”
Section: Bacterial Diseasesmentioning
confidence: 91%
“…In general, the incidence of gaping-jaw larvae increases with increasing temperature (Pittman et al 1989(Pittman et al , 1990a, an environmental factor that might cause increased bacterial activity and increase larval swimming activity. However, it should be noted that the gaping jaw condition is not related to the total number of bacteria in the rearing water (Opstad & Bergh 1993 (Bergh et al 1992b(Bergh et al , 1997. The exact nature of the gaping jaw syndrome remains unresolved.…”
Section: Gaping Jawmentioning
confidence: 99%
See 2 more Smart Citations
“…Bergh and colleagues [22] observed that, when starting its first feeding, the intestinal flora of the Atlantic halibut (Hippoglossus hippoglossus) changed from a prevalence of Flavobacterium spp. to Aeromonas spp./Vibrio spp.…”
Section: Use Of Probiotic In Aquaculturementioning
confidence: 99%